Dispositivos de asistencia circulatoria. Estado actual. Mechanical circulatory support devices, state of the art. - Dr. Angel M. Paredes Cordero; Lic. Alexei Suárez Rivero; Dra. Nadia Sánchez Torres; Dr. Geovedys Martínez (ECIMED, 2010)
Introduction To improve the quality of life of patients with terminal heart failure has beenthe motive of decades of investigation on ventricular assistance devices.This effort was stimulated by the increasing prevalence of this disease andits bad prognosis.Discussion There are several classifications for mechanical circulatory support devices.They can be classified according to the time of use for which they were design.Class I devices are of very short time of use (from hours to days), theyare use when an early full recover is expected or when a minimal interventionon the patient is desired. Class II devices are use when an intermediatesupport time is expected (days to weeks), but functional recovery is expectedto take longer. Class IIIa devices are intended for extended use(months to years). There are three main subcategories of extended use accordingto the therapeutic intention; as a therapeutic bridge to recovery/improved quality of life, as a bridge to transplant, and or as a permanentand definitive therapy. Class IIIb includes all devices that do not havedirect blood contact and is further subdivided into active and passive devices.Conclusions The present limitations of an artificial heart provide solid reasons for preferringa less invasive approach with the left ventricular assistance devices.On the other hand the large experience acquired with the use of such deviceshas demonstrated the feasibility of prolong the survival in an efficientmanner, and with an acceptable quality of life. The results of the REMATCHtrial were the key to demonstrated the superiority of the use of this devicesover the pharmacological therapy (in terminal patients), by showing improvementsin quality of life, survival and diminished overall costs. New horizonsin the treatment of heart failure including the possibility of enhancingthe natural potential for recovery of the failing myocardium by associatedpharmacological support or cell therapy is currently exciting much interestamong research and clinical cardiologists, and raising a lot of hope amongpatients. The development of new axial pumps has led to smaller sized devices,prolonged times of use and fewer device related complications.